2016
DOI: 10.1016/j.carbon.2015.10.048
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-dependent chemical state of the nickel catalyst for the growth of carbon nanofibers

Abstract: Nickel is one of the most commonly used catalysts for the growth of carbon which is clearly dependent on the growth temperature. Our findings reconcile the longstanding debate on the contradictory models (i.e. Ni-assisted growth, Ni 3 C 1-x -assisted growth and Ni 3 C-assisted growth) for the catalytic growth CNFs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
30
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 52 publications
5
30
0
Order By: Relevance
“…61 Group (b) spacings could be assigned either to rh-Ni 3 C or to fcc-Ni. According to these findings, previous own work, and the literature on this material system, the initial Ni-rich phase of NCT type I is assigned to rh-Ni 3 C. 57,[62][63][64] The cross-sectional TEM image of NCT type II (Fig. 1d) shows the formation of a Ni-enriched layer appearing darker than the SiO 2 substrate and the resin glue on top of the film, which is used for TEM specimen preparation.…”
Section: Resultssupporting
confidence: 61%
“…61 Group (b) spacings could be assigned either to rh-Ni 3 C or to fcc-Ni. According to these findings, previous own work, and the literature on this material system, the initial Ni-rich phase of NCT type I is assigned to rh-Ni 3 C. 57,[62][63][64] The cross-sectional TEM image of NCT type II (Fig. 1d) shows the formation of a Ni-enriched layer appearing darker than the SiO 2 substrate and the resin glue on top of the film, which is used for TEM specimen preparation.…”
Section: Resultssupporting
confidence: 61%
“…This situation is analogous to catalyst poisoning or coking mechanisms in classical heterogeneous catalysis. 112 We emphasize that this highly bulk supersaturated nature at all processing stages and the intrinsically high carbon arrival rates from the surroundings are hallmark features of the thermal evolution mechanism in such metal/carbon nanocomposites, which clearly separates this class of materials from other metal–carbon systems where carbon influx to the interface can be controlled at lower rates, such as in balanced heterogeneous catalysis reactions 112 , 113 or graphene 35 42 and CNT 45 59 growth from Ni catalysts.…”
Section: Discussionmentioning
confidence: 97%
“…[82] In another carbon nanofiber growth study with nickel as the growth substrate, it was found that nickel can be present in three stages during the growth process:N i 3 Ca t5 73 K, composite formation of Ni-Ni 3 C 1Àx at 673-773 Ka nd Ni metal at 873 K. They also note that no stable nickel carbides can be formed, but that metastable species are often presenta tl ower temperatures( below 1373K). [83] Ni-W 2 Cs upported on activated carbon has been shown to be comparablya ctive to noble metal catalysts in hydrocracking of woody biomass to form ethylene glycol. [84] Nickelm etal can be carburized to form Ni 3 C, which occurs in small amounts duringm ethanation with CO gas as the reactant at 538 K. [85]…”
Section: Biomass Conversion and Catalysts For Related Processesmentioning
confidence: 99%
“…The formation of carbon nanofibers and incorporated nickel carbide could only occur after the initial reduction of Ni 2+ to Ni 0 by carbon containing precursors . In another carbon nanofiber growth study with nickel as the growth substrate, it was found that nickel can be present in three stages during the growth process: Ni 3 C at 573 K, composite formation of Ni‐Ni 3 C 1− x at 673–773 K and Ni metal at 873 K. They also note that no stable nickel carbides can be formed, but that metastable species are often present at lower temperatures (below 1373 K) . Ni‐W 2 C supported on activated carbon has been shown to be comparably active to noble metal catalysts in hydrocracking of woody biomass to form ethylene glycol .…”
Section: Mechanisms Of In Situ Carburizationmentioning
confidence: 99%